2021
DOI: 10.1177/1403494821993721
|View full text |Cite
|
Sign up to set email alerts
|

Association between educational level and smoking cessation in an 11-year follow-up study of a national health survey

Abstract: Aims: There is a lack of longitudinal, population-based studies on the association between education and smoking cessation. A more thorough examination of this association is needed to address inequalities in smoking. Methods: The longitudinal Health 2000 Survey and Health 2011 Survey, representing the Finnish population aged ⩾30 years, were analysed. Of the 1352 baseline daily smokers, 945 (70%) provided a smoking status at the follow-up. The analytic sample size was 884 (excluding the follow-up occasional sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Thus, these groups should be targeted in smoking prevention and smoking cessation services. The results of the current study were consistent with a previous study on changes in smoking behaviour during COVID-19 within the Italian population [13], as well as with a Finnish study conducted before the COVID-19 pandemic that showed a higher probability of smoking cessation among men and older age groups [29]. Our findings also corroborate prior results on the association between mental health aspects related to COVID-19 and increased smoking [11,13,18]; experiences of increased loneliness and reduced social contact due to COVID-19 were associated with increased smoking among the general population.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, these groups should be targeted in smoking prevention and smoking cessation services. The results of the current study were consistent with a previous study on changes in smoking behaviour during COVID-19 within the Italian population [13], as well as with a Finnish study conducted before the COVID-19 pandemic that showed a higher probability of smoking cessation among men and older age groups [29]. Our findings also corroborate prior results on the association between mental health aspects related to COVID-19 and increased smoking [11,13,18]; experiences of increased loneliness and reduced social contact due to COVID-19 were associated with increased smoking among the general population.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results observed in this study at the ecological level. Similarly, it has been observed that people with higher socioeconomic status are more likely to quit smoking among the general adult population [ 70 ]. In fact, of the millions of people that tobacco will kill in 2030, more than 80% will live in low- and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Now, if we take into account the fact that the majority of our sample belongs to a lower social class (77.3% men and 59.8% women), this could justify a higher prevalence of active smokers, since several studies have found that smoking is more common in people belonging to lower socioeconomic levels, where smoking is more accepted within their social and work networks, with less feeling of guilt and less social support. As is the case of the OEDA labour survey (2020) of the Spanish Ministry of Health, in which 35.6% of workers smoke daily, the typical smoker is a man under 24 years of age, with a low educational level, and a manual worker in hospitality, construction, sales, or unemployed [65]; moreover, social classes with a higher socioeconomic level and a higher level of education are more likely to give up smoking if they have started it, whether due to feelings of guilt, social norms, and/or family pressures [66][67][68][69]. In our study, we found a relationship between the four IR indices and smoking, with an increased risk in smokers-which has also been described in other studies [70].…”
Section: Discussionmentioning
confidence: 99%